Implementation of Monopoly Game in Collaborative Learning to Improve Mastery of Trading Materials for Class XI IPS 2 SMA Negeri 6 Berau (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This classroom action research is intended to solve one of the learning problems, namely decreasing motivation and mastery of economic material by applying monopoly games in collaborative learning to increase mastery of trading materials. This research was conducted in two cycles and applied to class XI IPS-2 in the Odd semester of the 2022-2023 academic year at SMA Negeri 6 Berau, East Kalimantan. The results showed that there was an increase in the average value of the summative test, which was 63.15 (cycle 1) to 78.41 (cycle 2). Monopoly games in collaborative learning can improve the mastery of trading materials in class XI IPS 2 students of SMA NEGERI 6 Berau, Even Semester of the 2022-2023 Academic Year. Monopoly games in collaborative learning can also be implemented in other subjects, students in other schools, of course with adjustments as necessary.